A method of additive manufacturing of a medical porous Ti-6Al-4V alloy material

CN122913518APending Publication Date: 2026-10-16GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611243022.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有技术中,用于骨缺损修复的医用多孔Ti-6Al-4V合金支架,通常采用激光选区熔化(SLM)技术直接成形,但是采用该技术所得的医用多孔Ti-6Al-4V合金支架存在如下问题:(1)多孔支架支柱内部致密,缺乏物质传输通道;由于采用接近全致密的工艺参数,支柱内部为实体金属;成骨细胞也无法迁入支柱内部,骨整合仅能发生在支架支柱外表面,长期植入后支架中心区域易出现坏死或结合薄弱;(2)表面纳米结构缺失,生物活性不足

Benefits of technology

1、本发明的制备方法通过设计的多孔点阵三维模型,依托单胞内部的拓扑镂空设计,在点阵单胞、宏观点阵体系中构建全维度贯通的连通孔隙网络,孔隙孔径精准匹配成骨细胞的迁移尺寸阈值,可引导成骨细胞从支架外表面逐步迁入点阵支柱的内部区域,实现从表层到核心的全支架域骨整合,并通过精准调控SLM成形参数使激光能量输入可控偏离全致密成形窗口,可在点阵支柱内部原位生成孔径稳定分布微小的连通微米孔隙网络,再结合微弧氧化处理,全表面实现生物活性强化,大幅提升成骨细胞的黏附与增殖效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of manufacturing methods for additive manufacturing medical porous Ti-6Al-4V alloy material, comprising: design has the porous lattice three-dimensional model of predetermined porosity, wherein, porous lattice three-dimensional model is formed by a plurality of periodic array arrangement porous cell;Select Ti-6Al-4V alloy powder, by selective laser melting technology forming step S1 porous lattice three-dimensional model, make in-situ formation connected micron pore network inside strut, obtain forming support;Micro-arc oxidation treatment is carried out to forming support, and all surfaces including the inner wall of micron pore network are constructed nanoscale rough texture.The above preparation method is designed by porous lattice three-dimensional model, relies on the topological hollowing-out design in cell, constructs full-dimension through connected pore network in lattice cell, macroscopic lattice system, then combines micro-arc oxidation treatment, realizes biological activity strengthening on whole surface, substantially improves the adhesion and proliferation efficiency of osteoblast.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical materials technology, and in particular to a method for manufacturing a porous medical Ti-6Al-4V alloy material using additive manufacturing. Background Technology

[0002] The medical porous Ti-6Al-4V alloy scaffold uses medical-grade Ti-6Al-4V titanium alloy as the matrix and constructs a controllable porous structure inside through additive manufacturing and other technologies. The elastic modulus can be adjusted to 3~28GPa, which is far lower than the 110GPa of dense titanium alloy. It can perfectly match the mechanical range of human cancellous bone / cortical bone, fundamentally avoiding the "stress shielding" effect caused by traditional dense implants, and significantly reducing the risk of bone resorption and implant loosening after long-term implantation.

[0003] In the prior art, medical porous Ti-6Al-4V alloy scaffolds used for bone defect repair are usually formed directly using selective laser melting (SLM) technology. However, the medical porous Ti-6Al-4V alloy scaffolds obtained by this technology have the following problems: (1) The interior of the porous scaffold strut is dense and lacks material transport channels. Due to the use of near-fully dense process parameters, the interior of the strut is solid metal. Osteoblasts cannot migrate into the interior of the strut, and bone integration can only occur on the outer surface of the strut strut. After long-term implantation, the central area of ​​the scaffold is prone to necrosis or weak bonding. (2) The surface nanostructure is missing, resulting in insufficient biological activity. The surface of the existing struts is mostly micron-level rough structure, lacking more refined nanoscale textures (such as nano-pits, nanorods, etc.). Numerous studies have shown that nano-rough structures can significantly promote protein adsorption and regulate cell adhesion and differentiation. Their absence will lead to poor osteogenic activity and slow improvement in the bonding strength of the bone-implant interface.

[0004] Therefore, there is an urgent need to develop a medical porous Ti-6Al-4V alloy scaffold that can solve problems such as lack of material transport channels inside the scaffold, lack of surface nanostructures, and insufficient bioactivity, so as to simultaneously achieve mechanical adaptation, material transport, and enhanced bioactivity. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for manufacturing a porous medical Ti-6Al-4V alloy material by additive manufacturing, so as to solve the above-mentioned traditional technical problems.

[0006] This invention is achieved using the following technical solution: A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional model of a porous lattice with a predetermined porosity, wherein the three-dimensional model of the porous lattice is formed by multiple porous unit cells arranged in a periodic array. In this step, the overall elastic modulus of the scaffold is locked at 12~28GPa through the design of a porous lattice three-dimensional model, which perfectly matches the mechanical range of human bone tissue. This eliminates the stress shielding effect of traditional dense titanium alloy implants from the root. At the same time, relying on the topological hollow design inside the unit cell, a fully interconnected network of pores is constructed in the porous unit cell (micro-unit) and the macro lattice system (macro-entity). The pore size is precisely matched with the migration size threshold of osteoblasts, which can guide osteoblasts to gradually migrate from the outer surface of the scaffold into the internal area of ​​the lattice pillar, realizing full scaffold domain bone integration from the surface to the core. This completely breaks through the technical bottleneck of traditional single macro lattice scaffolds that can only achieve surface bone ingrowth.

[0007] S2: Using Ti-6Al-4V alloy powder, a porous lattice three-dimensional model from step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W-200W, scanning speed 500mm / s-800mm / s, scanning spacing 100μm-150μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. In this step, by precisely controlling the SLM forming parameters, the laser energy input is controllably deviated from the fully dense forming window. The molten pool cannot achieve complete spreading and full overlap, resulting in controllable, incompletely melted gaps between individual molten pools and adjacent pools, and between the current printed layer and the next. These micro-gaps spontaneously interconnect in three-dimensional space, generating a stable, interconnected micro-pore network within the lattice strut without the need for additional pore-forming agents. This pore system completely permeates the inner and outer surfaces of the strut, seamlessly connecting with the macroporous channels of the macro-lattice, constructing a multi-level interconnected material transport pathway covering the entire scaffold area. This guides osteoblasts, tissue fluid, and nutrients to gradually penetrate from the outer surface of the scaffold to the core area, completely overcoming the technical bottleneck of traditional fully dense lattice scaffolds that can only achieve superficial bone ingrowth. This fundamentally solves the clinical pain point of insufficient bone integration within large implants.

[0008] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material.

[0009] In this step, the plasma from the micro-arc discharge can penetrate to all internal and external surfaces, including the inner walls of the micron-sized pores inside the support, simultaneously constructing a uniform nanoscale TiO2 rough texture, achieving enhanced bioactivity across the entire surface, and significantly improving the adhesion and proliferation efficiency of osteoblasts. Compared to conventional scaffolds, the osseointegration speed of this scaffold is further improved.

[0010] Furthermore, in step S1, the configuration of the porous unit cell is selected from one of the following: body-centered hexagonal structure, face-centered cubic structure, dodecahedral structure, octahedral structure, and minimal surface structure.

[0011] Furthermore, in step S1, the configuration of the porous lattice three-dimensional model is selected from one of the following: body-centered hexagonal structure, face-centered cubic structure, dodecahedral structure, octahedral structure, and minimal surface structure.

[0012] The pores of the above-mentioned structures are all three-dimensionally fully interconnected, maintaining a stable macroscopic connectivity rate. They can seamlessly connect with the micron-sized pores inside the support pillars generated in situ by subsequent SLM, forming a multi-level material transport channel covering the entire area of ​​the scaffold, ensuring that cells and body fluids can permeate into the core of the scaffold.

[0013] Furthermore, in step S1, the construction of the porous lattice three-dimensional model is carried out using the computer-aided design software Materialise Magics.

[0014] Furthermore, in step S1, the diameter of the struts in the porous lattice 3D model is 500μm-700μm, such as 500μm, 550μm, 600μm, 650μm, 700μm, etc., and the porosity is 60%-70%, such as 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, etc. This strut diameter range (the diameter range of the connecting rods in the porous unit cell) provides sufficient space for the subsequent in-situ generation of interconnected micron-sized pores by SLM, preventing structural collapse after the internal pores are connected due to excessively thin struts, ensuring the compressive strength of the scaffold, and meeting the high load requirements of orthopedic implantation.

[0015] Furthermore, in step S2, the particle size distribution of Ti-6Al-4V alloy powder is 15μm-53μm. Spherical powder in this particle size range has the best flowability. When the powder layer thickness is 30μm, uniform and dense coating can be achieved without obvious agglomeration or powder shortage defects, ensuring the stability of the printing process. In addition, the powder particle size is highly matched with the micron pore size inside the pillar to be generated. The gaps between the incompletely melted residual powder can naturally form interconnected pores, and there will be no uncontrolled problem of pores being too large or too small.

[0016] Furthermore, in step S2, the Ti-6Al-4V alloy powder, by mass percentage, comprises: 5.5%-6.8% Al, 3.5%-4.5% V, 0.01%-0.1% Ta, 0.05%-0.5% TiO2, with the remainder being Ti. In this formulation, the Al and V contents fully comply with the ISO 5832-3 standard for medical titanium alloys, ensuring the basic mechanical properties and biocompatibility of the matrix, meeting the core requirements of orthopedic implants. The low Ta content, as a medical inert element, can slightly improve the alloy's resistance to body fluid corrosion without introducing any biotoxicity risks. The low proportion of TiO2 can generate trace amounts of Ti-O reinforcing phase in the SLM molten pool, slightly improving the surface hardness of the scaffold and serving as a nucleation core for subsequent micro-arc oxidation, resulting in more uniform nanotexture formation without any issues of brittle phase precipitation due to excessive addition.

[0017] Furthermore, in step S2, the pore size of the connected micron-sized pore network is 50μm-100μm, such as 50μm, 53μm, 58μm, 60μm, 62μm, 65μm, 68μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, and 100μm. Pores of this size will not be blocked by the nanotexture during micro-arc oxidation, allowing the plasma from the micro-arc discharge to easily penetrate the inner walls of the pores, simultaneously generating uniform nano-active textures on all inner surfaces, thus achieving enhanced bioactivity across the entire surface.

[0018] Further, in step S3, the electrolyte for micro-arc oxidation treatment is an aqueous aluminate solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 25℃-30℃. Under these conditions, the high voltage of the bidirectional pulse can drive the plasma to penetrate the internal micron-sized pores, simultaneously generating a uniform nano-TiO2 texture on all inner and outer walls of the scaffold, preventing any blind spots in the pores from being missed. The low-temperature electrolyte avoids local overheating and ablation of the thin-walled lattice structure, while also inhibiting pore blockage caused by excessively rapid film growth, ensuring the connectivity of all channels. The parameter combination of 150 Hz frequency + 0.5 duty cycle can generate crater-like nanopores with an average pore size of 80~200 nm, ensuring both bioactivity and preventing excessive consumption of the substrate and reduction of mechanical properties.

[0019] Furthermore, step S3 also includes a post-processing step: After the micro-arc oxidation process, a post-processing step of full-pore depth cleaning is added: the obtained additively manufactured medical porous Ti-6Al-4V alloy material is completely immersed in deionized water at 80℃-100℃ and ultrasonically cleaned for 10min-30min under a 40kHz ultrasonic field. Utilizing the low surface tension of high-temperature water and the ultrasonic cavitation effect, the water flow is driven to penetrate into the 50μm-100μm micron-sized pores inside the stent, completely peeling off and removing unmelted Ti-6Al-4V powder and electrolyte deposits remaining in the dead corners of the pores. Subsequently, the stent is transferred to anhydrous ethanol solution and cleaned for another 10min-30min under the same ultrasonic parameters. The high volatility of ethanol is used to quickly replace the residual water in the pores, preventing water from forming a liquid seal in the closed micropores. Ultimately, the three-level pore network of the entire stent area is 100% connected, with no powder or impurities clogging the pores, while ensuring that the nanoscale rough texture of all inner and outer surfaces is completely preserved without mechanical wear and shedding.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The preparation method of the present invention utilizes a designed porous lattice three-dimensional model and relies on the topological hollowing design inside the unit cell to construct a fully interconnected network of pores in the lattice unit cell and macroscopic lattice system. The pore size is precisely matched to the migration size threshold of osteoblasts, which can guide osteoblasts to gradually migrate from the outer surface of the scaffold into the internal region of the lattice pillar, realizing full scaffold domain osteointegration from the surface to the core. By precisely controlling the SLM forming parameters, the laser energy input can be controllably deviated from the fully dense forming window, which can generate a stable distribution of tiny interconnected micro-pores in situ inside the lattice pillar. Combined with micro-arc oxidation treatment, the entire surface achieves enhanced bioactivity and significantly improves the adhesion and proliferation efficiency of osteoblasts.

[0021] 2. The preparation method of the present invention also has the following advantages: (1) Significantly improves the depth and uniformity of bone tissue ingrowth. Existing technologies only allow bone tissue to grow into the surface, while in this invention, the micron-sized pores that extend from the inside of the support to the outside provide a three-dimensional transport path for nutrient solution, oxygen and cells, realizing the "full scaffold domain" ingrowth of bone tissue and avoiding central necrosis.

[0022] (2) Synergistic enhancement of osteogenic activity and interfacial bonding strength. The synergistic effect of micron-sized pores and surface nano-roughness can not only accelerate the adsorption and anchoring of biomacromolecules such as fibrin, but also induce osteoblast differentiation and rapid mineralization, ultimately forming mechanical and chemical bonding between bone tissue and implant at the micro and nanoscale, thereby improving the bone-implant bonding strength.

[0023] (3) Mechanical properties are better matched with host bone. By adjusting the SLM parameters to control the micron porosity inside the support, the local stiffness and strength of a single support can be independently adjusted without changing the macroscopic shape. The overall apparent elastic modulus is closer to that of human cancellous and compact bone, effectively alleviating the stress shielding effect.

[0024] (4) The alloy material obtained by the preparation method of the present invention has an elastic modulus of 15-23 GPa, a compressive yield strength of 19-26 MPa, an adhesion rate of more than 90%, and an ALP expression level of 2.0-2.6 U / mg protein. Detailed Implementation

[0025] The present invention will now be further described in conjunction with specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0026] Example 1 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0027] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0028] Example 2 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 700 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0029] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0030] Example 3 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 70%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0031] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0032] Example 4 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 200W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0033] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0034] Example 5 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 800mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0035] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0036] Example 6 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 150μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0037] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0038] Example 7 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 190W, scanning speed 600mm / s, scanning spacing 120μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0039] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0040] Example 8 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.1%Ta, 0.05%TiO2, and the remainder is Ti.

[0041] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0042] Example 9 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.1%TiO2, and the remainder is Ti.

[0043] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0044] Example 10 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a face-centered cubic structure, and the porous unit cells have a face-centered cubic structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0045] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0046] Example 11 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple periodically arranged porous unit cells; the three-dimensional porous lattice model has a dodecahedral structure, and the porous unit cells have a dodecahedral structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0047] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0048] Example 12 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple periodically arranged porous unit cells; the three-dimensional porous lattice model has an octahedral structure, and the porous unit cells have an octahedral structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0049] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0050] Example 13 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a minimal surface structure, and the porous unit cells have a minimal surface structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0051] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0052] Example 14 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0053] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0054] The obtained additively manufactured medical porous Ti-6Al-4V alloy material was completely immersed in deionized water at 80°C and ultrasonically cleaned for 20 minutes under a 40kHz ultrasonic field. Then the stent was transferred to anhydrous ethanol solution and cleaned for another 20 minutes under the same ultrasonic parameters.

[0055] Comparative Example 1 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 100W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0056] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0057] Comparative Example 2 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 300W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0058] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0059] Comparative Example 3 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 1000mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 0.05%TiO2, and the remainder is Ti.

[0060] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0061] Comparative Example 4 A method for additively manufacturing a porous Ti-6Al-4V alloy material for medical use includes the following steps: S1: Design a three-dimensional porous lattice model with a predetermined porosity, wherein the three-dimensional porous lattice model is formed by multiple porous unit cells arranged in a periodic array; the three-dimensional porous lattice model has a body-centered hexagonal structure, and the porous unit cells have a body-centered hexagonal structure; the pillar diameter is 600 μm, and the porosity is 65%; S2: Ti-6Al-4V alloy powder with a particle size distribution of 15μm-53μm is selected. The porous lattice three-dimensional model of step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W, scanning speed 500mm / s, scanning spacing 100μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. The Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 6%Al, 4%V, 0.01%Ta, 2%TiO2, and the remainder is Ti.

[0062] S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material. The electrolyte for the micro-arc oxidation treatment is an aluminate aqueous solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 28℃.

[0063] Performance testing 1. Mechanical properties: Compressive yield strength and elastic modulus were tested in accordance with GB / T 7314-2017 "Metallic materials - Compression test at room temperature".

[0064] 2. Adhesion rate test: The direct adhesion counting method under the framework of GB / T 16886.5 Medical Device Biocompatibility Test was adopted. The number of adherent cells was counted by fluorescent staining 24 hours after inoculation, and the adhesion rate was calculated.

[0065] 3. ALP expression level test: The industry-standard p-nitrophenyl phosphate colorimetric method was used, and the osteogenic activity of bone tissue engineering materials was evaluated according to the general specifications. After 7 days of culture, ALP activity was quantitatively detected at a wavelength of 405nm using an enzyme-linked immunosorbent assay (ELISA) reader.

[0066] 4. The test results are shown in Table 1.

[0067] Table 1 The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A method for manufacturing a porous medical-grade Ti-6Al-4V alloy material using additive manufacturing, characterized in that, Includes the following steps: S1: Design a three-dimensional model of a porous lattice with a predetermined porosity, wherein the three-dimensional model of the porous lattice is formed by multiple porous unit cells arranged in a periodic array. S2: Using Ti-6Al-4V alloy powder, a porous lattice three-dimensional model from step S1 is formed by selective laser melting technology. The process parameters are set as follows: laser power 180W-200W, scanning speed 500mm / s-800mm / s, scanning spacing 100μm-150μm, powder layer thickness 30μm. A strip scanning strategy is adopted, and the adjacent layers are rotated by 67° to form a connected micron-level pore network in situ inside the support, thus obtaining the formed support. S3: Perform micro-arc oxidation treatment on the molded scaffold to construct a nanoscale rough texture on all surfaces, including the inner wall of the micron-scale pore network, to obtain the additive manufacturing medical porous Ti-6Al-4V alloy material.

2. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 1, characterized in that, In step S1, the configuration of the porous unit cell is selected from one of the following: body-centered hexagonal structure, face-centered cubic structure, dodecahedral structure, octahedral structure, and minimal surface structure.

3. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 2, characterized in that, In step S1, the configuration of the porous lattice three-dimensional model is selected from one of the following: body-centered hexagonal structure, face-centered cubic structure, dodecahedral structure, octahedral structure, and minimal surface structure.

4. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 1, characterized in that, In step S1, the diameter of the pillars of the porous lattice 3D model is 500μm-700μm, and the porosity is 60%-70%.

5. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 1, characterized in that, In step S2, the particle size of the Ti-6Al-4V alloy powder is 15μm-53μm.

6. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 5, characterized in that, In step S2, the Ti-6Al-4V alloy powder, by mass percentage, has the following chemical composition: 5.5%-6.8% Al, 3.5%-4.5% V, 0.01%-0.1% Ta, 0.05%-0.5% TiO2, with the remainder being Ti.

7. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 1, characterized in that, In step S2, the pore size of the connected micron-sized pore network is 50 μm-100 μm.

8. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 1, characterized in that, In step S3, the electrolyte for micro-arc oxidation treatment is an aqueous aluminate solution, and the treatment conditions are: positive voltage 550 V, negative voltage -200 V, frequency 150 Hz, duty cycle 0.5, and electrolyte temperature 25℃-30℃.

9. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 1, characterized in that, In step S3, after the micro-arc oxidation treatment is completed, a post-treatment process of full-pore depth cleaning is added: The obtained additively manufactured medical porous Ti-6Al-4V alloy material was completely immersed in deionized water at 80℃-100℃ and ultrasonically cleaned for 10min-30min under an ultrasonic field. Then the stent was transferred to anhydrous ethanol solution and cleaned for another 10min-30min under the same ultrasonic parameters.

10. The method for manufacturing the additively manufactured medical porous Ti-6Al-4V alloy material according to claim 9, characterized in that, The frequency of the ultrasound is 40 kHz.